Effective endovascular reconstruction using multiple leo stents and silk flow-diverting stents for asymptomatic extracranial internal carotid artery dissection: a case report - Soetanto, Gamaliel Wibowo; Usman, Fritz Sumantri (International Journal of Research in Medical Sciences, 2024)
Extracranial carotid artery dissection (ECAD), although infrequent, represents the predominant form of artery dissection within the brain. It accounts for 25% of young-onset ischemic strokes in adults. Its atypical presentation and limited availability of high-quality evidence underscore the importance of precision medicine in its management. This study aimed to illustrate a combined approach utilizing multiple scaffolding Leo stents and Silk flow-diverting stents to manage asymptomatic ECAD a week after the onset of acute ischemic stroke. A 40-year old Indian male with uncontrolled hypertension was admitted due to acute vestibular syndrome. His brain computed tomography (CT) scan showed cerebellar infarct. However, his angiographic cervical CT scan showed asymptomatic ECAD, which was confirmed with digital subtraction angiography. He was therefore managed with optimal antihypertensive agents and dual antiplatelet. The endovascular reconstruction procedure initiated one week after the onset of stroke by employing one scaffolding Leo stent and one Silk flow-diverting stent at his right internal carotid artery. He was discharged three days following the endovascular procedure and presented no complications until three-month follow-up. This safe approach could be considered for individuals with ECAD to help prevent secondary strokes, particularly among those in the productive age group.